Numerical and Experimental Investigation on Combustion Characteristics and Pollutant Emissions of Pulverized Coal and Biomass Co-Firing in a 500 kW Burner - Rachapat Chaiyo; Jakrapop Wongwiwat; Yanin Sukjai (Fuels)
The global shift towards clean energy has been driven by the need to address global warming, which is exacerbated by economic expansion and rising energy demands. Traditional fossil fuels, particularly coal, emit more pollutants than other fuels. Recent studies have shown significant efforts in using biomass as a replacement or co-firing it with coal. This is because biomass, being a solid fuel, has a combustion mechanism similar to that of coal. This study investigates the co-firing behavior of pulverized coal and biomass in a semi-combustion furnace with a 500 kW heat input, comprising a pre-chamber and a main combustion chamber. Using computational fluid dynamics (CFD) simulations with ANSYS Fluent 2020 R1, the study employs species transport models to predict combustion reactions and discrete phase models (DPM) to track fuel particle movement. These models are validated against experimental data to ensure accurate predictions of mixed fuel combustion. The research examines various biomass-to-coal ratios (0%, 25%, 50%, 75%, and 100%) to understand their impact on combustion temperature and emissions. Results show that increasing the biomass ratio reduces combustion temperature due to biomass’s lower heating value, higher moisture content, and larger particle size, leading to less efficient combustion and higher CO emissions. However, this temperature reduction also correlates with lower NOx emissions. Additionally, biomass’s lower nitrogen and sulfur content contributes to further reductions in NOx and SO2 emissions. Despite biomass having higher volatile matter content, which results in quicker combustion, coal demonstrates a higher carbon burnout rate, indicating more efficient carbon combustion. The study concludes that while pure coal combustion efficiency is higher at 87.7%, pure biomass achieves only 77.3% efficiency. Nonetheless, increasing biomass proportions positively impacts emissions, reducing harmful NOx and SO2 levels.